Rapid antigen group A streptococcus test to diagnose pharyngitis: a systematic review and meta-analysis. - Emily H Stewart; Brian Davis; B Lee Clemans-Taylor; Benjamin Littenberg; Carlos A Estrada; Robert M Centor (PLoS ONE)
Background Pharyngitis management guidelines include estimates of the test characteristics of rapid antigen streptococcus tests (RAST) using a non-systematic approach. Objective To examine the sensitivity and specificity, and sources of variability, of RAST for diagnosing group A streptococcal (GAS) pharyngitis. Data sources MEDLINE, Cochrane Reviews, Centre for Reviews and Dissemination, Scopus, SciELO, CINAHL, guidelines, 2000-2012. Study selection Culture as reference standard, all languages. Data extraction and synthesis Study characteristics, quality. Main outcome(s) and measure(s) Sensitivity, specificity. Results We included 59 studies encompassing 55,766 patients. Forty three studies (18,464 patients) fulfilled the higher quality definition (at least 50 patients, prospective data collection, and no significant biases) and 16 (35,634 patients) did not. For the higher quality immunochromatographic methods in children (10,325 patients), heterogeneity was high for sensitivity (inconsistency [I(2)] 88%) and specificity (I(2) 86%). For enzyme immunoassay in children (342 patients), the pooled sensitivity was 86% (95% CI, 79-92%) and the pooled specificity was 92% (95% CI, 88-95%). For the higher quality immunochromatographic methods in the adult population (1,216 patients), the pooled sensitivity was 91% (95% CI, 87 to 94%) and the pooled specificity was 93% (95% CI, 92 to 95%); however, heterogeneity was modest for sensitivity (I(2) 61%) and specificity (I(2) 72%). For enzyme immunoassay in the adult population (333 patients), the pooled sensitivity was 86% (95% CI, 81-91%) and the pooled specificity was 97% (95% CI, 96 to 99%); however, heterogeneity was high for sensitivity and specificity (both, I(2) 88%). Conclusions RAST immunochromatographic methods appear to be very sensitive and highly specific to diagnose group A streptococcal pharyngitis among adults but not in children. We could not identify sources of variability among higher quality studies. The present systematic review provides the best evidence for the wide range of sensitivity included in current guidelines.